INTEGRATING SOCIAL, SOCIETAL, CULTURAL, AND SITUATIONAL CONTEXTS TO DEVELOP PRAGMATICS COURSE LEARNING MATERIALS: PRELIMINARY STUDY (INTEGRASI SOSIAL, SOSIAL, BUDAYA, DAN KONTEKS SITUASIONAL UNTUK MENGEMBANGKAN MATERI PEMBELAJARAN PRAGMATIK: STUDI AWAL) - Rahardi, R. Kunjana (Universitas PGRI Sumatera Barat, 2019)
The industrial revolution 4.0 clearly demands language learners to keep evolving to adapt to the environmental development. The learning of Pragmatics in the higher education cannot be based on the pragmatic concepts as what has happened recently, but it must be integrated with the fundamental research findings in the relevant fields of Pragmatics. This R & D raises the issue of: How the research findings on the situational and socio-cultural contexts are integrated in the material development of the Pragmatics course. The development of the Pragmatics course learning materials which integrates research findings in the pragmatic contexts is based on R & D model. The development output is then validated by experts, and piloted restrictively to several students. In the next step, the product output of the material development is revised to improve, which then will be published and disseminated. Due to the time constraint, this paper limits the scope of discussion only on the result of preliminary study. The other steps belong to the scope of different papers.